Characterization of bacteria associated with omphalitis in chicks (Bangladesh Veterinarian, 2013)
This study was conducted to isolate and characterize the bacteria present in cases of omphalitis in chicks. Yolk swabs (n = 60) were aseptically collected from affected chicks and cultured for isolation and identification of bacteria. E. coli, Salmonella and Staphylococci were identified. Bacteria were tested for sensitivity to ten common antibiotics. E coli isolates were sensitive to chloramphenicol and resistant to nalidixic acid, ampicillin, amoxycillin, ciprofloxacin, tetracycline, gentamicin, sulphamethoxazole and erythromycin. Salmonella were sensitive to ciprofloxacin and resistant to tetracycline. Staphylococci were sensitive to ampicillin, amoxycillin, ciprofloxacin, gentamicin, sulphamethoxazole, erythromycin, chloramphenicol and kanamycin and resistant to nalidixic acid and tetracycline. The existence of multi-drug resistance emphasises the need to prevent omphalitis in chicks by hygiene. DOI: http://dx.doi.org/10.3329/bvet.v29i2.14344 Bangl. vet. 2012. Vol. 29, No. 2, 63-68